Global warming executive predictions - Levy, Mitchell; Mudhol, Jitendra (Cupertino, CA : HappyAbout.info, 2008)
2007 was a turning point in the consciousness of the planet. It was a turning point where we no longer asked the question'Is global warming real?', but perceived global warming as reality. Ok, so if we now believe, what can we do about it? Some answers are contained in this book. The real answers, however, will unfold over the next couple of years. We need to act, we need to invest, we need to change, we need to invest in protecting the future.
Description based on print version record.
Requires Adobe Digital Editions (file size: 412 KB).
Keywords: Global warming; Electronic books